Variation of the rfb gene clusters in Salmonella enterica. - Xiang, S H (1993)
In order to explore the genetic variation of O antigens of Salmonella enterica, we surveyed 164 strains (132 serovars) belonging to 45 serogroups, using 25 mostly single-gene rfb DNA probes for colony hybridization. The results revealed that strains within a serogroup have very similar or identical rfb genes. At least three of the four rhamnose genes were detected in all 17 serogroups reported to contain rhamnose, and one or more were detected in three others. The likelihood of being detected decreased in the order rfbB, rfbC, rfbA, and rfbD, which is the map order, suggesting a gradient of divergence. Mannose pathway genes were much less conserved, and of 27 groups reported to contain mannose or mannose derivatives colitose or fucose, only 9 hybridized to the rfbM and rfbK probes. Dideoxyhexose genes were found only in groups reported to contain dideoxyhexoses. Group D2, which had not been studied previously, appears to resemble group D1, with the substitution of one gene from group E1 to give a change in one linkage. In contrast to sugar pathway genes, sugar transferase genes did not in general hybridize to strains of other groups outside the closely related groups A, B, and D, with the exception of the galactose transferase gene also shared by groups C2, C3, and all E groups.